Thiopurines: Use them or lose them? International survey on current and future use of thiopurines in inflammatory bowel disease. Issue 12 (December 2021) - Sousa, Paula; Ministro, Paula; Armuzzi, Alessandro; Dignass, Axel; Høivik, Marte Lie; Barreiro-de Acosta, Manuel; Vavricka, Stephan; Saad-Hossne, Rogério; Kotze, Paulo Gustavo; Peyrin-Biroulet, Laurent; Magro, Fernando
Abstract: Background and aims: The role of thiopurines in therapeutic algorithms of Crohn's disease (CD) and Ulcerative colitis (UC) is being questioned. This work aimed to investigate current practice and future perspectives of Inflammatory Bowel Disease (IBD) physicians regarding the efficacy, safety, and role of precision medicine with thiopurines in IBD. Methods: A 29-questions web-based survey was developed and distributed to IBD physicians worldwide. Results: We collected the complete answers of 408 physicians from 50 countries. Most participants were experienced physicians in IBD; 26.0% met our definition of "IBD expert". Four physicians reported to not use thiopurines in clinical practice. Most respondents used thiopurines in monotherapy and in combination therapy, both in CD and UC. Respondents tended to consider thiopurines as drugs with a good safety profile, with the agreement of 61.5% of the overall cohort. A minority of physicians ( 6%) considered that thiopurines will not be used in the future in IBD patients, while 57.8% believed that these drugs will still be used, in mono and combination therapy. Conclusion: Despite the many emerging treatments in IBD, according to the beliefs of most physicians surveyed, thiopurines will still be an important part of the treatment algorithm of both CD and UC.